Morphine in Combination with Ketamine Improves Cervical Cancer Pain and Suppresses Immune Function via the JAK3/STAT5 Pathway - Yurong Jiang; Tong Li; Yi Qian; Xiaoming Zuo; Jinmei Liu (Pain Research and Management)
Background. The role of ketamine as an adjuvant for morphine in the treatment of cancer pain and immune functions has been confirmed. This study aimed to explore the role of morphine and ketamine on cancer pain and T cells of patients with cervical cancer (CC). Methods. T cells were isolated from peripheral blood mononuclear cells (PBMC) of CC patients by positive selection using anti-CD3 beads. The isolated T cells were assigned into three groups: the control group, the morphine group, and the morphine + ketamine (Mor + Ket) group. The percentages of CD4+ and CD8+ were analyzed by flow cytometry. The levels of interferon (IFN)-γ, interleukin (IL)-2, and IL-17 and the corresponding mRNA expression in vitro were determined using ELISA and qRT-PCR, respectively. Western blotting was used for detection of JAK3/STAT5 pathway-related proteins after naltrexone treatment in vitro. Afterwards, all the patients were further divided into the morphine group and the Mor + Ket group in accordance with the principles of the randomized and double-blind method to assess pain intensity. Results. Our in vivo results showed that drug combinations relieved cancer pain more effectively than morphine intervention. The in vitro results demonstrated that the combination of morphine and ketamine may decrease CD4+ percentage, CD4+/CD8+ ratio, and the levels of IFN-γ, IL-2, and IL-17 via the JAK3/STAT5 pathway. Conclusions. Our finding indicated that morphine-ketamine combination could improve cancer pain and repress immune function via the JAK3/STAT5 pathway in the progression of CC.